THE INFLUENCE OF PRODUCT DESIGN ON PURCHASING DECISIONS WITH BRAND IMAGE AS A MODERATING VARIABLE - Basnendar Herry Prilosadoso; Indri Yani; Ana Yuliana; Mahmuddin Mahmuddin; Sriwanti Belani5 (ITB AAS Indonesia Surakarta, 2024)
This research is a quantitative study with an explanatory approach, namely an approach that relies on a number of previous studies as the main reference for analyzing, varying, and refining the research being conducted. The data in this article is primary data that researchers obtained from a number of credible sources, namely Suzuki Sales Marketing spread throughout Indonesia as many as 500 people. The data were analyzed using the smart PLS 4.0 analysis tool with the following hypothesis. The result in this article show that the results go hand in hand with the hypothesis because the P-Values are positive and are at a significance level of 0.05, namely 0.014. This indicates that the better the Product Design, the more consumers will be attracted to decide to make a Purchase Decision. Next, in the next line, it can be concluded that the Brand Image variable can moderate the influence of the Product Design variable on Purchasing Decisions because the same thing is that the P-Values are positive and below the significance level of 0.05, namely 0.00. Thus, it can be concluded that the first and second hypotheses in this article can be accepted. Keywords: Product Design, Purchasing Decisions, Brand Image